MAPKs Influence Pollen Tube Growth by Controlling the Formation of Phosphatidylinositol 4, 5-Bisphosphate in an Apical Plasma Membrane Domain. Issue 12 (22nd November 2017) - Hempel, Franziska; Stenzel, Irene; Heilmann, Mareike; Krishnamoorthy, Praveen; Menzel, Wilhelm; Golbik, Ralph; Helm, Stefan; Dobritzsch, Dirk; Baginsky, Sacha; Lee, Justin; Hoehenwarter, Wolfgang; Heilmann, Ingo
Abstract : The production of regulatory membrane phospholipids required for polar tip growth of pollen tubes is controlled by mitogen-activated protein kinases. Abstract: An apical plasma membrane domain enriched in the regulatory phospholipid phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2 ] is critical for polar tip growth of pollen tubes. How the biosynthesis of PtdIns(4, 5)P2 by phosphatidylinositol 4-phosphate 5-kinases (PI4P 5-kinases) is controlled by upstream signaling is currently unknown. The pollen-expressed PI4P 5-kinase PIP5K6 is required for clathrin-mediated endocytosis and polar tip growth in pollen tubes. Here, we identify PIP5K6 as a target of the pollen-expressed mitogen-activated protein kinase MPK6 and characterize the regulatory effects. Based on an untargeted mass spectrometry approach, phosphorylation of purified recombinant PIP5K6 by pollen tube extracts could be attributed to MPK6. Recombinant MPK6 phosphorylated residues T590 and T597 in the variable insert of the catalytic domain of PIP5K6, and this modification inhibited PIP5K6 activity in vitro. PIP5K6 interacted with MPK6 in yeast two-hybrid tests, immuno-pull-down assays, and by bimolecular fluorescence complementation at the apical plasma membrane of pollen tubes. In vivo, MPK6 expression resulted in reduced plasma membrane association of a fluorescent PtdIns(4, 5)P2 reporter and decreased endocytosis without impairing membrane association of PIP5K6. Effects of PIP5K6 expression on pollen tube growth and cell morphology were attenuated by coexpression of MPK6 in a phosphosite-dependent manner. Our data indicate that MPK6 controls PtdIns(4, 5)P2 production and membrane trafficking in pollen tubes, possibly contributing to directional growth.